2018
DOI: 10.1007/s00181-018-1527-3
|View full text |Cite
|
Sign up to set email alerts
|

Critical slowing down as an early warning signal for financial crises?

Abstract: Financial crises have repeatedly been coined as a potential application area in the recent literature on constructing early warning signals through identifying characteristics of critical slowing down on the basis of time series observations. To test this idea, we consider four historical financial crises-Black Monday 1987, the 1997 Asian Crisis, the 2000 Dot-com bubble burst, and the 2008 Financial Crisis-and investigate whether there is evidence for critical slowing down prior to these market collapses. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…Potential applications include the observation of animals through camera traps, disease surveillance sampling in wildlife or movements in stock prices, which are all examples of incidence-type data. Notably, a substantial number of studies on ecosystem data, climate data and financial data have observed inconsistencies in statistical indicators [16, 22, 23, 29]. Although we found the Poisson process to be overdispersed in the context of epidemiology, it provides a broad framework which can be extended to many other infectious disease systems using the incoming transition probabilities into the infectious class.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Potential applications include the observation of animals through camera traps, disease surveillance sampling in wildlife or movements in stock prices, which are all examples of incidence-type data. Notably, a substantial number of studies on ecosystem data, climate data and financial data have observed inconsistencies in statistical indicators [16, 22, 23, 29]. Although we found the Poisson process to be overdispersed in the context of epidemiology, it provides a broad framework which can be extended to many other infectious disease systems using the incoming transition probabilities into the infectious class.…”
Section: Discussionmentioning
confidence: 71%
“…Discrepancies in statistical signatures have been discovered in a variety of historical datasets known to be going through a critical transition: from climate systems to stock markets, to applications with ecological field data [16, 22, 23]. These studies observed unexpected characteristic traits of common EWS, such as identifying a decreasing trend in variance or standard deviation, leading to a discussion on the robustness of indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding temporal early warning indicators have been found, for example, for past population collapses from archaeological site ages [72], contemporary electricity grid blackouts from load data [73], or the bursting of housing bubbles from market data [74]. Generic early warning indicators give mixed results before financial crises [75] but specific indicators, such as attempts by traders to gather financial information from the internet, increase [76] and network indicators can reveal structural instability [77]. For tipping points in collective behaviour more generally, the content, amount and network structure of activity on social media can provide early warning signals [78].…”
Section: Early Warning Signalsmentioning
confidence: 97%
“…In the literature, complexity theory is usually applied to research critical transitions in eco-systems (Scheffer et al, 2009). Some studies also apply it to financial data, by using complexity indicators to detect financial crises (Guttal et al, 2016, Diks et al 2015and Quax et al, 2013. The added value of our paper is that we apply complexity theory to regime shifts in the configuration of interest rates, linking them to the increase of excess liquidity.…”
Section: Figure 1 Excess Liquidity In Euro Areamentioning
confidence: 99%